Pengaruh Penggunaan Fitur Posting Ulang terhadap Kepuasan Pengguna Instagram pada Generasi Z - Desy Ratna Sari; Rendra Widyatama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effect of using the repost feature ion instagram user satisfaction among generation Z. The main research question is whether the use of the repost feature affects user satisfaction levels. The study employs a quantitative approuch using a survey method involving 100 respondents selected via purposive sampling, with the criteria being active instagram users who have used the repost feature. Data were collected via a questionnaire using a likert scale and analyzed using descriptive stastistical techniques as well as simple linier regression. The result indicate that the use of the repost feature has a positive and significant effect on instagram user satisfaction among generation Z. The mot dominant motives for use are the need for information and self expression. These findings suggest that the repost feature functions not only as a means of sharing conten but also as a medium for fulfilling users psychological and social needs. This study contributes to the development of the Use and Gratification theory by emphasizing the importance of feature level analysis in understanding social media user behavior.